El software qlikview como herramienta para el aprendizaje de la correcta toma de decisiones empresariales en los estudiantes de la Universidad Técnica de Cotopaxi, de la carrera de ingeniería comercial período 2012-2013 - Tapia Guerrero, Gladis Victoria (2015)
When the company manager or owner or, any person begins to detect the need for Smart Business solution, it may be for several causes, but the most common is a situation which is responsible of the different required areas to dispose more information than they can provide their actual management system. It is for this reason which today, that we will want, it is to get results as soon as possible because they will be living at the technology age; therefore, company always try to be aware of the most relevant because through them have managed to optimize times, financial, material and human resources are allowing what before it is taking to make in a month, at present it may make it even less than half of that time. That is, which this research, aim is to provide the QlikView Software, this is designed for taking immediate decisions in any company type where it could be used, it should not take ruls based only on data or figures many times isolated to the reality or many cases, just by sampling, but taking into account each and every one of the data business own cases, without the need to use different programs. QlikView Software joins whole company database and immediately it throws desired results which allows experiencing a new and dynamic way of making decisions that will be effective to develop a guide and this is detailed step by step, for a better software understanding operation.